(untitled) (African Journal of Biomedical Research, 2021)
The antioxidant properties of Moringa oleifera leaf have been found beneficial in several conditions characterized by oxidative stress. It had gained wider use albeit lack of study on its effective dose. It is also known that standard antioxidant could be prooxidants at doses higher than the recommended. The present study investigated the effects of high dose of methanol extract of Moringa oleifera leaf (MEMO) on testicular oxidative stress and histology of cryptorchid rats. Thirty-two male Wistar rats were assigned into four groups. Group A was sham-operated and given distilled water, groups B, C and D were bilaterally cryptorchid and treated with distilled water, low dose MEMO (200mg/kg) and high dose MEMO (500mg/kg), respectively. After three weeks of treatments, the left testis was obtained, weighed and assessed for histopathological variation while, superoxide dismutase (SOD) and gamma Glutamyl Transferase (GGT) activities were determined in the right testis. Testicular SOD activity reduced while GGT was increased in the cryptorchid compared with the control. Low dose MEMO-treated cryptorchid had increased SOD with reduced GGT activity compared to the untreated cryptorchid rats. At high dose of MEMO, SOD activity was significantly reduced while GGT activity increased. Testicular histology showed distorted cytoarchitecture and degeneration of germ cells in the cryptorchid rats. This was ameliorated in the low dose MEMO-treated group while there was no difference between the testicular cytoarchitecture of untreated cryptorchid and the high dose MEMO-treated rats. High dose of Moringa oleifera leaf extract has no effect on the testes of experimentally-induced bilateral cryptorchid rats.